Estandarización de una prueba de ELISA para detección de anticuerpos contra el herpesvirus bovino -1 en suero lácteo (1996)
ABSTRACT: The objective of this study was to standardize an ELISa technique for serological testing of BHV-1 in milk serum. This technique is expected to facilitate large serological screening in milking cows. For this purpose, 69 samples from Nt and ELISA positives and 105 Nt and ELISA negatives animals were used. The average of optical densities for the negative samples was 0.04 +/- 0.02 and for the positive the averge was 0.20 +/- 0.06 based on this results we set a delta value of optical density of 0.08 as the cut off point for positivity. This value gives a sensibility of 100% and specificity of 94%. The concordance between serum Nt and serum ELISA and milk serum ELISA was of 97%. The standardization of this ELISA provides a new instrument not only for the characterization of the infection in our country but also for its control and eventual eradication. Finally we discuss the possibility of further optimizing by using straight milk or milk serum pools to facilitate further the massive screening of large populations.